BCL-xL-selective BH3 mimetic sensitizes rhabdomyosarcoma cells to chemotherapeutics by activation of the mitochondrial pathway of apoptosis. (1st January 2018) - Faqar-Uz-Zaman, Sara Fatima; Heinicke, Ulrike; Meister, Michael Torsten; Vogler, Meike; Fulda, Simone
Abstract: BH3 mimetics are a promising new class of anticancer agents that inhibit antiapoptotic BCL-2 proteins. Here, we report that BH3 mimetics selectively targeting BCL-xL, BCL-2 or MCL-1 (i.e. A-1331852, ABT-199, A-1210477) act in concert with multiple chemotherapeutic agents (i.e. vincristine (VCR), etoposide (ETO), doxorubicin, actinomycin D and cyclophosphamide) to induce apoptosis in rhabdomyosarcoma (RMS) cells. Similarly, genetic knockdown of BCL-xL primes RMS cells to VCR- or ETO-induced cell death, highlighting the importance of BCL-xL in mediating chemotherapy resistance in RMS. A-1331852 and VCR or ETO cooperate to stimulate caspase activation and caspase-dependent apoptosis, since the broad-range caspase inhibitor zVAD.fmk rescues cells from cell death. Molecular studies reveal that VCR/A-1331852 co-treatment causes profound mitotic arrest, which initiates phosphorylation of BCL-2, thereby promoting its inactivation. Also, A-1331852 and VCR or ETO act together to trigger BAX and BAK activation, followed by loss of mitochondrial membrane potential (MMP). Consistently, overexpression of BCL-2 or MCL-1 markedly reduces VCR/A-1331852- or ETO/A-1331852-mediated apoptosis, underscoring that mitochondrial apoptosis represents a key event in synergistic drug interaction. In conclusion, our findings provide a rationale for the combination of BH3 mimetics with conventional chemotherapeutic agents to increase the chemosensitivity of RMS. Graphical abstract: Image 1 Highlights: BCL-xL -selective BH3 mimetic (i.e. A-1331852) chemosensitizes rhabdomyosarcoma cells. Genetic knockdown of BCL-xL enhances chemotherapy-induced apoptosis. Mitochondrial apoptosis pathway mediates synergy of A-1331852 and chemotherapeutics.